Analisis Keberhasilan Model Teaching at the Right Level (TaRL) dalam Meningkatkan Kemampuan Membaca Siswa Kelas Rendah di Sekolah Dasar - Bunyamin, Bunyamin; Anfal, Wahyuddin; Mariamah, Mariamah (Bima Journal of Elementary Education, 2025)
This study aims to analyze the effectiveness of the Teaching at the Right Level (TaRL) model in improving the reading skills of lower-grade elementary school students at SDN 11 Pajo, Dompu Regency. The urgency of this research lies in the low literacy achievement among elementary students, particularly in identifying main ideas, answering literal questions, making inferences, and drawing conclusions from texts. The research employed a quantitative approach with a quasi-experimental method using a one-group pretest–posttest design. The subjects consisted of 28 second-grade students selected through purposive sampling. Data were collected through a validated reading comprehension test and classroom observations of TaRL-based learning implementation. Data analysis was conducted using descriptive statistics, N-Gain calculations, and paired sample t-tests. The findings indicate a significant increase in the mean score from 54.8 in the pretest to 84.6 in the posttest, with a mean difference of 29.8 points and a significance level of p < 0.001. The N-Gain analysis showed that 39.3% of students were in the high category, 53.6% in the medium category, and only 7.1% in the low category. These results confirm that the TaRL model is not only effective in enhancing literacy outcomes but also in reducing learning gaps through differentiated instruction. This study concludes that TaRL is highly relevant to the implementation of the Independent Curriculum, contributes theoretically to the development of early literacy strategies, and provides practical implications for teachers and policymakers in strengthening reading skills as the foundation for continuous learning.